Sources of world economic growth - Nghiep, Le THanh (Washington, D.C., U.S.A. : World Bank, 1983)
This study classifies the world major economies into five groups according to their development phases, and identifies their source of growth
Includes bibliographical references
hza 01/02/2019
Loans
Keywords: Economic history; Economic growth; Input-output analysis; Economic policy